2003
DOI: 10.1076/ocii.11.4.277.18260
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of intraocular inflammatory disease in Japan

Abstract: These results confirm a continued high frequency of VKH disease and sarcoidosis, but suggest a decreased frequency of Behçet's disease and an increased frequency of tuberculosis. Roughly one-half of the patients required systemic treatment in addition to local therapy, and ocular and/or systemic complications developed in one-fifth of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
6
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(107 citation statements)
references
References 2 publications
6
87
6
8
Order By: Relevance
“…Most of the previous studies reported equal sex distribution (3,4,10,12,20,21). There are, however, studies stating a female (6,13,16,22) or male (9,(23)(24)(25) predominance. Female predominance has been explained by the greater proportion of chronic disease in women (6).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Most of the previous studies reported equal sex distribution (3,4,10,12,20,21). There are, however, studies stating a female (6,13,16,22) or male (9,(23)(24)(25) predominance. Female predominance has been explained by the greater proportion of chronic disease in women (6).…”
Section: Discussionmentioning
confidence: 74%
“…Consul et al (26) suggested that men tend to seek medical attention more often than women in agricultural societies, and this might explain the reported male predominance. BD is the leading cause of uveitis in series from Turkey (9,19), Saudi Arabia (27), Israel (4), China (7,28), Iran (29), and Japan (13). BD cases constituted nearly onethird of our patient population and there was a 3-fold male predilection in this subgroup, accounting for nearly 20% of the whole population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result correlates with other studies where they have reported the cause of uveitis being unknown in approximately 30-60% of patients. [4][5][6][7][8][9][10][11][12] Systemic disease, which could be considered to be related to the intraocular inflammation, was determined in 26.6% of all cases on the basis of history, ocular examination and laboratory investigations. It was similar to the study done by Rothova et al where systemic disease related to intraocular inflammation was diagnosed in 26%.…”
Section: Methodsmentioning
confidence: 99%